Bimetal nano assembly as well as preparation method and application thereof
Through coordination-mediated self-assembly of bimetallic HfCu-polyphenols, nanoassemblies that can be deassembled and deeply penetrated in the tumor microenvironment were prepared, which solved the problem of limited penetration depth of Hf-based nanoradiotherapy sensitizers, and achieved efficient radiotherapy sensitization and tumor suppression, while reducing side effects.
Patent Information
- Application Number
- CN202311603822.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-11-28
AI Technical Summary
The limited penetration and diffusion depth of existing Hf-based nanoradiotherapy sensitizers in tumors leads to limited radiotherapy sensitization effects, and there are concerns about side effects of normal tissues.
Using coordination-mediated self-assembly of bimetallic HfCu-polyphenols, uniform size HfCu-polyphenol nanoparticles were prepared, and the NO donor L-Arg was efficiently loaded through hydrogen bonding and benzene ring conjugation to achieve deassembly and deep penetration of tumor microenvironment response.
This bimetal nanoassembly can be deassembled in the tumor microenvironment, improve tumor hypoxia, produce a variety of free radicals, sensitizing radiotherapy, efficiently inhibit tumors, and reduce side effects on normal tissues.
Smart Images

Figure CN119499369A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a bimetallic nanoassembly and a preparation method and application thereof. Background Art
[0002] Radiation therapy, or RT, is one of the most effective strategies currently used in clinical cancer treatment. The basic principle of RT is that high-energy X-rays or γ-rays directly interact with the DNA of cells, causing DNA damage, or indirectly react with water molecules to generate reactive oxygen free radicals (ROS) (such as superoxide, hydrogen peroxide, hydroxyl radicals, etc.). ROS can damage DNA or other cell components and induce cell apoptosis and necrosis. However, RT alone is usually not enough to completely eliminate tumor cells. The main reasons include: (1) Hypoxia is an important feature of solid tumors. The imbalance between oxygen supply and demand leads to tumor hypoxia. The free radicals generated by RT will be reduced by the large number of sulfhydryl groups in the hypoxic environment, resulting in a reduction in tumor cell DNA damage caused by radioresistance, which in turn leads to tumor invasion and metastasis, immune escape, etc., reducing the efficacy of RT; (2) Tumors have low radiation absorption of high-energy rays. Radiotherapy often requires high-dose radiation, which inevitably damages normal tissues around the tumor. In addition, glutathione (GSH) free radical scavengers that are highly expressed in the tumor microenvironment (TME) also tend to reduce the efficacy of RT.
[0003] The study found that compared with the radiosensitizers represented by iodine-based small molecules used in clinical practice, inorganic nanomaterials with high Z atomic numbers such as Au, Pt, TaO x , HfO2 (clinical phase III radiosensitizer), Hf-MOF, etc. have the effect of inducing radiation dose enhancement in tumors, which can partially concentrate the ionization energy in the tumor and are radiosensitizers that can improve and sensitize the efficacy of radiotherapy. Among them, Hf-based nano-radiotherapy sensitizers have the advantages of good radiotherapy sensitization effect, good biosafety and high CT signal enhancement ability, and their synthesis cost is much lower than that of precious metal nano-radiotherapy sensitizers. However, the ultra-small size of Hf-based nano-radiotherapy sensitizers is easily metabolized from the tumor, and the tumor retention time is too short. The size of Hf-based radiotherapy sensitizers currently used in clinical practice, such as HfO2, is about 50nm, and this size has limited penetration and diffusion depth in the tumor, thus restricting its radiotherapy sensitization effect. Therefore, it is imperative to simply and low-cost construct an Hf-based radiotherapy sensitization strategy that can penetrate deep into the tumor, have a long retention time, and significantly increase the free radicals in the tumor to sensitize radiotherapy. This strategy needs to improve intratumor hypoxia under TME response while producing multiple free radicals to sensitize radiotherapy and reduce side effects on normal tissues. The combined treatment strategy of size-reducible / disassembled engineered nanomedicines responsive to the biological microenvironment provides a new idea for solving the above problems.
[0004] NO is a typical endogenous gas signal molecule with concentration-dependent physiological properties. For example, when the heart is stimulated by ischemia and hypoxia, NO within a certain dose range has physiological mechanisms such as anti-inflammatory, anti-apoptotic, anti-oxidative stress, and promotion of angiogenesis, which has an important protective effect on the heart. NO is also an effective radiosensitizer, and its main radiosensitization mode is twofold: 1) A certain dose of NO can react with superoxide anions to generate reactive nitrogen radicals (RNS), which are more likely to cause tumor cell apoptosis than ROS; 2) NO can restore abnormal tumor blood vessels to normal, dilate tumor blood vessels, and thus increase blood perfusion and oxygen supply. In order to give full play to the function of NO, the dose and duration of NO treatment need to be strictly controlled, otherwise it will lead to completely opposite results. However, there is currently a lack of NO delivery methods that can meet both needs.
[0005] L-arginine (L-Arg) is currently regarded as an effective substitute for NO precursors due to its excellent biosafety. However, as a water-soluble small molecule, L-Arg is difficult to load efficiently in nanomedicines, and its efficiency in catalyzing the production of NO in vivo is too low, with a short half-life (less than 5s) and a short diffusion distance (20-160 microns). It is urgent to achieve its efficient loading and controlled release in tumors. Studies have found that ROS generated during tumor treatment processes such as radiotherapy and photodynamic therapy can further catalyze the decomposition of L-Arg efficiently, thereby achieving external light-induced NO gas therapy to improve tumor hypoxia. Phenolic structures, such as gallic acid, tannic acid, and catechol, can show strong affinity with a wide range of materials through non-covalent interactions (such as hydrogen bonds, π-π interactions, coordination bonds, and electrostatics), especially with specific metals. Phenolic self-assembled nanosystems are excellent drug carriers and have been used in photodynamic therapy, immunotherapy, radiodynamic therapy, and their combined therapies. However, most of the reported metal polyphenol assembly systems are single metals, and there are few reports on bimetallic polyphenol nanoassembly systems. In particular, there are currently no reports on bimetallic-polyphenol nanoself-assembled radiotherapy sensitizers for deep tumor penetration and improvement of hypoxia. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a bimetallic nanoassembly and its preparation method and application. The coordination-mediated bimetallic HfCu-polyphenol self-assembly method provided by the present invention is simple, environmentally friendly, low-cost, and has good biocompatibility. It provides a synthesis strategy for a radionuclide-labeled HfCu-bimetallic nanoassembly structure that can improve tumor hypoxia, and it also provides a new idea for clinical diagnosis and treatment of internal and external radiotherapy tumors.
[0007] Specifically, the first aspect of the present invention provides a method for preparing a bimetallic nanoassembly, comprising:
[0008] A) mixing a phenolic polymer with a surfactant solution;
[0009] B) mixing the solution obtained in step A) with a hafnium chloride solution;
[0010] C) mixing the solution obtained in step B), a cross-linking agent and a copper sulfate solution;
[0011] D) adjusting the pH of the solution obtained in step C) to 7-9, centrifuging and precipitating to obtain Hf-Cu polyphenol nanoassemblies.
[0012] The present invention provides a simple, environmentally friendly, low-cost, and biocompatible coordination-mediated bimetallic HfCu-polyphenol self-assembly method, and obtains HfCu-polyphenol nanoparticles with uniform size and adjustable particle size in the range of 95 to 150 nm by pH. After loading the NO donor L-arginine (abbreviated as HLC), the nano self-assembled particles can achieve tumor microenvironment response disassembly and deep intratumoral penetration and retention, while NO gas therapy improves tumor hypoxia, copper death cooperates with radiotherapy sensitization and efficiently inhibits tumors and has potential application prospects in reducing side effects on normal tissues.
[0013] Furthermore, step B) further comprises mixing the solution obtained in step A) with an aqueous solution of hafnium chloride and then adding an L-arginine solution, preferably stirring for 2 to 5 minutes after adding the L-arginine solution.
[0014] In the present invention, in step D), the solution obtained in step C) is adjusted to pH 7-9, preferably pH 8, by using NaOH or ammonia solution.
[0015] In the present invention, by using NaOH solution or ammonia solution to adjust the pH to 7-9, especially when the pH is 8, the bimetallic nanoassembly system can have an optimal particle size of about 100 nm, and reducing the pH value can increase the particle size.
[0016] Preferably, the Hf-Cu polyphenol nano-assembly is obtained by centrifugation at a rotation speed of 8000-15000 rpm and precipitation and washing.
[0017] Preferably, the pH is adjusted to 8 with NaOH solution, centrifuged at 8000-15000 rpm, and the precipitate is washed to obtain the Hf-Cu polyphenol nanoassembly; preferably, the pH is adjusted to 8 with 0.5-0.6M NaOH solution, stirred, centrifuged at 8000-15000 rpm for 2-4 minutes, and the precipitate is washed with deionized water.
[0018] Preferably, step D) further comprises mixing the Hf-Cu polyphenol nanoassembly with deionized water, adding a BSA solution, centrifuging and washing to obtain BSA-modified HfCu-polyphenol nanoparticles.
[0019] Further preferably, in step D), the BSA-modified HfCu-polyphenol nanoparticles are further subjected to radionuclide 99 Tc labeling.
[0020] In the present invention, the HLC nano self-assembled particles modified with protein BSA have high 99 The Tc labeling rate is 88.23%. This radionuclide-labeled nanomedicine can achieve SPECT imaging-guided tracing of deep intratumoral penetration effects and radiotherapy inside and outside the tumor. At the same time, it reduces the dose of X-rays used during radiotherapy, thereby reducing side effects on normal tissues.
[0021] Preferably, the radionuclide labeling comprises: using acetic acid-sodium acetate buffer to prepare the BSA-modified HfCu-polyphenol nanoparticles into HLC@BSA solution, adding stannous chloride solution and sodium pertechnetate solution, ultrasonically dispersing and then centrifuging and washing to obtain radionuclide-labeled bimetallic Hf-Cu nano self-assembly HLC@BSA@ 99m Tc.
[0022] Preferably, the Hf-Cu polyphenol nanoassembly is mixed with deionized water and then added with BSA solution, stirred in the dark for 12 to 24 hours, and then centrifuged at 8000 to 10000 rpm for 3 to 4 minutes, and the precipitate is washed with deionized water to obtain BSA-modified HfCu-polyphenol nanoparticles, which are then subjected to radionuclide 99 Tc labeling, obtain BSA modification and nuclide 99 Tc-labeled bimetallic HfCu-polyphenol self-assembled particles HLC@BSA. Further preferably, the mass volume ratio of Hf-Cu polyphenol nanoassembly, deionized water and BSA solution is 10-20 mg: 1-2 mL: 1-2 mL; the concentration of the BSA solution is 10-20 mg / mL.
[0023] Preferably, in step D), the radionuclide labeling comprises: preparing the BSA-modified HfCu-polyphenol nanoparticles into HLC@BSA solution using acetic acid-sodium acetate buffer, adding stannous chloride solution and sodium pertechnetate solution, and washing by centrifugation after ultrasonic dispersion.
[0024] Further preferably, the acetic acid-sodium acetate buffer is an acetic acid-sodium acetate buffer with a pH of 4.6 to 5.0; the HLC@BSA solution is a 1 to 2 mg / mL HLC@BSA solution; the concentration of the stannous chloride solution is 2 to 3 mg / mL; the activity of the sodium pertechnetate solution is 5 to 8 mCi; the volume ratio of the HLC@BSA solution to the stannous chloride solution is 1 to 2 mL: 20 to 30 μL; the volume ratio of the stannous chloride solution to the sodium pertechnetate solution is 1 to 2: 20 to 28. Preferably, ultrasonic dispersion is performed for 10 to 30 minutes, and then centrifuged at a speed of 8000 to 12000 rpm for 5 to 10 minutes, and the precipitate is added with deionized water and centrifuged and washed continuously.
[0025] Preferably, the phenolic polymer comprises tannic acid; and / or the cross-linking agent is formaldehyde solution.
[0026] More preferably, the mass ratio of poloxamer, tannic acid and hafnium chloride is 0.15-0.3:1-2:0.32-0.64.
[0027] In the present invention, the molar ratio of Hf and Cu can be controlled by the feed ratio of raw materials; preferably, in the hafnium chloride aqueous solution and the copper sulfate solution, the molar ratio of hafnium chloride to copper sulfate is (0.00005-0.0001):(0.00002-0.00004), preferably 0.0001:0.00002.
[0028] In a second aspect, the bimetallic nanoassembly provided by the present invention is Hf-Cu-polyphenol nanoparticles; preferably BSA modified with nuclides 99 Tc-labeled bimetallic Hf-Cu-polyphenol self-assembled particles;
[0029] Preferably, the molar ratio of Hf to Cu is 2.6:1;
[0030] And / or, the particle size of the bimetallic nanoassembly is 95-150 nm.
[0031] The bimetallic nanoassembly provided by the present invention is preferably prepared by the above-mentioned method for preparing the bimetallic nanoassembly.
[0032] In a third aspect, the present invention provides a bimetallic nanoassembly prepared by the above-mentioned method for preparing a bimetallic nanoassembly or the use of the above-mentioned bimetallic nanoassembly in preparing tumor therapeutic agents, antibacterial agents or environmental management agents.
[0033] Preferably, the tumor therapeutic agent includes a radiosensitizer.
[0034] In a fourth aspect, the present invention provides a tumor treatment device, comprising an X-ray laser and a bimetallic nanoassembly prepared by the above-mentioned bimetallic nanoassembly preparation method or the above-mentioned bimetallic nanoassembly.
[0035] The beneficial effects of the present invention are at least that: the present invention synthesizes bimetallic Hf-Cu-polyphenol nanoparticles HC by self-assembly at room temperature through a coordination-mediated strategy, wherein the ratio of Hf and Cu can be controlled by the feed ratio of the raw materials. This method is simple, green, and environmentally friendly, and can synthesize a large amount of bimetallic-polyphenol nano self-assembly system HC with good biocompatibility at one time. Then, the NO donor L-Arg is efficiently loaded through hydrogen bonding and benzene ring conjugation to obtain the HLC nano self-assembly structure. The dose of NO gas controlled catalytic release from L-Arg under the action of X-rays can improve tumor hypoxia, while copper death synergistic radiosensitization can effectively inhibit tumors, reduce the X-ray dose, and thus reduce side effects on normal tissues. In addition, the dual-modality imaging technology based on single-photon emission computed tomography / computed tomography (SPECT) can comprehensively utilize the functional information obtained by SPECT imaging and the anatomical structure information obtained by CT imaging, and has been used for rapid, efficient, and non-invasive diagnosis research of various tumors and cardiovascular diseases with the help of nano-contrast agents. Radionuclide technetium 99 Tc can release r-rays, has an ideal half-life (6.02h), requires a small dose, and is non-toxic. Its chemical properties and biological characteristics are suitable for labeling most medical imaging drugs. 99 Chelation of Tc, designed 99 Tc-labeled HLC (HLC@BSA@ 99m Tc). This radionuclide-labeled bimetallic HLC nano self-assembly can not only enhance the internal radiotherapy treatment effect of radioisotopes, but also improve the external radiotherapy of hypoxia combined with copper death sensitization Hf elements, generate multiple free radicals, and achieve deep intratumor penetration effect tracing of SPECT / CT imaging navigation, and effectively inhibit tumors. At the same time, the X-ray dosage is reduced, thereby reducing the side effects on normal tissues. In general, the present invention provides a synthesis strategy for nuclide-labeled HfCu-bimetallic nanoassembly structures that can improve tumor hypoxia, and it also provides a new idea for clinical diagnosis and treatment of internal and external radiotherapy tumors. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A flow chart for preparing a bimetallic nanoassembly provided in an embodiment of the present invention;
[0038] Figure 2 The morphology and element distribution diagrams of HB and HL provided in Example 1 of the present invention: (a) is a transmission electron microscope (TEM) image of Hf-BSA (HB), and the particle diameter is about 2-3 nm; (b) and (c) are scanning electron microscope (SEM) and TEM images of Hf-Cu polyphenol nanoassembly (HC), respectively, and the estimated particle size is about 95 nm; (d) is an energy spectrum diagram of Hf-Cu polyphenol nanoassembly; (e) is a high-angle dark field transmission HHAADF and element energy spectrum distribution diagram of Hf-Cu polyphenol nanoassembly;
[0039] Figure 3 TEM images of the disassembly of HLC in a simulated tumor microenvironment provided in Example 2 of the present invention: (a) and (b) are TEM images of Hf-Cu polyphenol and L-Arg nanoassembly HLC after being treated with a simulated tumor microenvironment solution (0.1 M H2O2+PBS 5.5) for 4 h and 12 h, respectively;
[0040] Figure 4 X-ray photoelectron spectra (XPS) of HB and HLC provided in Examples 1 and 2 of the present invention: (a) is the X-ray photoelectron spectra of Hf-BSA (HB) and HLC; (b)-(f) are the detailed X-ray photoelectron spectra of C, O, Hf, Cu, and N elements in HLC, respectively;
[0041] Figure 5 (a) The cloning effect diagram of 4T1 breast tumor cells by HLC and (b) the statistical data of the survival rate of 4T1 breast tumor cells in different treatment groups provided in Example 2 of the present invention;
[0042] Figure 6 The dose-dependent effect curve of X-ray radiotherapy sensitization provided in Example 2 of the present invention: (a) is a colony formation diagram of 4T1 breast tumor cells treated with control and Hf-Cu polyphenol nanoassembly HLC at different X-ray irradiation doses; (b) is the survival rate of 4T1 mouse breast tumor cells treated with control and HLC at different X-ray irradiation doses, HLC concentration: 50 μg / mL;
[0043] Figure 7 The dose-dependent toxic effect diagram of HB and HLC on tumor cells provided in Examples 1 and 2 of the present invention, the incubation time is 24h;
[0044] Figure 8 HB@BSA@ provided in Examples 1 and 3 of the present invention 99mTc(a) and HLC@BSA@ 99m In vivo SPECT / CT imaging of Tc (b) and distribution maps (c) and (d). DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] If no specific technology or conditions are specified in the embodiments of the present invention, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market.
[0047] Some embodiments of the present invention provide a method for preparing a bimetallic nanoassembly, the process is as follows: Figure 1 As shown. The radionuclide-labeled radiotherapy sensitizer provided in the embodiment of the present invention is an L-arginine-modified HfCu-polyphenol nano-engineered self-assembled particle, referred to as HLC, with a size of about 100nm. At a mild ambient temperature, it is obtained by a simple metal coordination-mediated self-assembly synthesis method, which does not require a complicated operation process, is simple, green, environmentally friendly, and has a high yield. This strategy not only has a simple assembly function, but also has a disassembly / disassembly property of intelligent response. This is mainly because HLC also has a degradable disassembly effect in response to the micro-acidic environment of the tumor. After intravenous administration, it has a higher permeability and long retention (EPR) effect than the ultra-small size Hf-BSA nanoparticles of 2 to 3nm, and can be disassembled from 100nm to a smaller size under the action of the acidic tumor microenvironment with high expression of H2O2 and the free radicals generated by radiotherapy. This new responsive disassembly strategy increases the deep penetration depth of HLC in the tumor. Moreover, the polyphenols used are plant extracts that are ubiquitous in nature, and the cross-linked polymer products are safe. At the same time, its abundant hydrogen bonds and π-π conjugated functional groups are important prerequisites for metal coordination and self-assembly of its nanoparticles. This type of degradable nano self-assembled particles is easily metabolized from the body, has no toxic side effects, and has high biosafety. Therefore, it is expected that HC / HLC particles will serve as a model system for the preparation of engineered nanoparticles and basic research in nanoscience, opening up a variety of application pathways, functions and properties, such as biomedicine and environmental governance, and have adjustable space.
[0048] Based on the high Z atomic number of Hf in HLC and its high proportion of self-assembly, it can enhance the radiotherapy effect. Combined with the free radicals generated by X-ray radiotherapy, it can controllably release NO in the NO donor L-arginine in HLC, thereby improving the effect of tumor hypoxia and sensitizing radiotherapy. Most importantly, due to the effective coordination of the Cu element in the bimetal, HLC exerts the copper death effect to further sensitize radiotherapy and effectively inhibit tumors. Furthermore, BSA-modified HLC is easy to carry out radionuclide 99 Tc-labeled, with high labeling rate, this 99 Tc-labeled HLC nano-self-assemblies can not only enhance the therapeutic effect of internal radiotherapy with radioisotopes, but also improve the external radiotherapy of hypoxia combined with copper-sensitized Hf elements, generate multiple free radicals, and realize SPECT imaging-guided tumor diagnosis and treatment and the tracing of its deep intratumoral penetration effect, which has potential application prospects in biology and clinical medicine.
[0049] Example 1
[0050] Synthesis of bimetallic HfCu-polyphenol nanoparticles (HC) via coordination-mediated self-assembly strategy
[0051] Take 0.032g of hafnium chloride (HfCl4) and add it to 4mL of deionized water to prepare an aqueous solution of hafnium chloride for later use. Take 0.015g of poloxamer (Pluronic F127) and add it to a mixed solution of 14mL of deionized water and 2mL of anhydrous ethanol. After ultrasonic dissolution, add 0.1g of tannic acid powder to it and stir for 2min until the tannic acid is completely dissolved and the solution appears light white. Add all the prepared hafnium chloride aqueous solution dropwise to the light white solution, and the solution will further turn white, and floccules will be generated. Then add 0.2mL of formaldehyde solution (37wt%) to the above solution, stir for 1min, then add 1mL of copper sulfate solution (0.5wt% CuSO4, 5mg), and continue stirring for 5min. Among them, the molar ratio of raw materials Hf to Cu is 5:1. Finally, adjust the solution pH to 8 with 0.5M NaOH and continue stirring for 1h. After stirring, the obtained solution was centrifuged at 10000 rpm for 4 min, and the obtained precipitate was washed with deionized water for 3 times to obtain pure Hf-Cu polyphenol nanoparticles (HC), which were freeze-dried for later use.
[0052] Comparative Example 1
[0053] Hf-BSA Nanoclusters (HB) and Their Nuclides 99 Synthesis of Tc-labeled Hf-BSA nanoclusters
[0054] Take 0.012g of hafnium chloride (HfCl4) powder and add it to 2mL of deionized water to dissolve and disperse evenly. Add the above solution to 2mL of BSA solution (10mg / mL) and stir for 2min. Add 0.5M NaOH solution to the above mixed solution to adjust the pH to 8. Stir the above solution in the dark for 12h. After stirring, transfer the solution to a dialysis bag for 48h of dialysis treatment, and change the water every 24h to obtain Hf-BSA nanoclusters HB.
[0055] Prepare 1mg / mL Hf-BSA solution with acetic acid-sodium acetate buffer system at pH=4.6, take 1mL of the above solution, add 20μL of stannous chloride solution (2mg / mL, SnCl2) and mix thoroughly, add 280μL of sodium pertechnetate solution (activity: 5mCi) to the above solution, and disperse by ultrasound for 30min. After the ultrasound, centrifuge at 12000rpm for 5min and collect the supernatant. Add 1mL of deionized water to the precipitate and wash it three times by centrifugation, and collect the supernatant each time. After the end, measure the activity of the supernatant and precipitate in the measuring well.
[0056] Example 2
[0057] Self-assembled L-arginine-containing bimetallic HfCu-polyphenol nanoparticles (HLC)
[0058] Take 0.032g of hafnium chloride (HfCl4) and add it to 4mL of deionized water to prepare a hafnium chloride aqueous solution for use. Take 0.015g of poloxamer (Pluronic F127) and add it to a mixed solution of 14mL of deionized water and 2mL of anhydrous ethanol, and ultrasonicate until the poloxamer dissolves. After dissolution, add 0.1g of tannic acid powder to it and stir for 2min until the tannic acid is completely dissolved and the solution appears light white. Add all the prepared hafnium chloride aqueous solution dropwise to the light white solution, the solution further turns white, and floccules are generated. Take 5mg of L-arginine and add it to the solution and stir for 2min. Then add 0.2mL of formaldehyde solution (37wt%) to the above solution, stir for 1min, then add 1mL of copper sulfate solution (0.5wt% CuSO4, 5mg), and continue stirring for 5min. Among them, the molar ratio of raw materials Hf to Cu is 5:1. Finally, the pH was adjusted to 8 with 0.5 M NaOH solution and stirring was continued for 1 h. The resulting solution was centrifuged at 10,000 rpm for 4 min, and the precipitate was washed 3 times with deionized water to obtain a pure Hf-Cu polyphenol nanoassembly (HLC). According to the ICP-MS test results, the molar ratio of Hf to Cu in the resulting assembly HC was 2.6:1.
[0059] Example 3
[0060] BSA modification and nuclide 99Tc-labeled bimetallic HfCu-polyphenol self-assembled nanoparticles
[0061] 20 mg of HfCu-polyphenol nanoparticles (HLC) prepared by the method of Example 2 were added to 2 mL of deionized water and dispersed uniformly by ultrasonication. The above solution was added to 2 mL of BSA solution (20 mg / mL) and stirred in the dark for 24 h. After stirring, the resulting solution was centrifuged at 10000 rpm for 4 min, and the precipitate was washed once with deionized water to obtain BSA-modified HfCu-polyphenol nanoparticles (HLC@BSA).
[0062] Prepare 1mg / mL HLC@BSA solution with acetic acid-sodium acetate buffer at pH=4.6, take 1mL of the above solution, add 20μL of stannous chloride solution (2mg / mL, SnCl2) and mix thoroughly, add 280μL of sodium pertechnetate solution (activity: 5mCi) to the above solution, ultrasonically disperse for 30min, centrifuge at 12000rpm for 5min, and collect the supernatant. Add 1mL of deionized water to the precipitate and continue centrifugation and washing three times. Collect the supernatant after each washing. After the end, measure the activity of the supernatant and precipitate in the measuring well to obtain 99 Tc-labeled HLC@BSA 99m Tc). and stored at 4°C.
[0063] Example 4
[0064] The same method as in Example 2 was used, except that the pH value of 0.5 M NaOH solution was adjusted to 7.5 instead of 8.0 M NaOH solution. The method of Example 3 was used to prepare BSA modified with nuclide. 99 Tc-labeled bimetallic HfCu-polyphenol self-assembled particles.
[0065] Example 5
[0066] The same method as in Example 4 was used, except that the amount of hafnium chloride was changed from 0.032 g to 0.016 g, and the molar ratio of hafnium to copper was changed from 5:1 to 2.5:1, to obtain a bimetallic-polyphenol self-assembly system with a varying ratio of Hf to Cu. The molar ratio of Hf to Cu in the obtained product HC was calculated to be 1.1:1 by ICP-MS. Then, the method of Example 3 was used to prepare BSA modified with nuclides. 99 Tc-labeled bimetallic HfCu-polyphenol self-assembled particles.
[0067] The morphology and element distribution diagram of HB and HL provided in Example 1 of the present invention ( Figure 2): (a) is the transmission electron microscope (TEM) image of Hf-BSA (HB), and the particle diameter is about 2-3nm; (b) and (c) are the scanning electron microscope (SEM) and TEM images of Hf-Cu polyphenol nanoassembly (HC), respectively, and the estimated particle size is about 95nm; (d) is the energy spectrum of Hf-Cu polyphenol nanoassembly; (e) is the high-angle dark field transmission HHAADF and element energy spectrum distribution of Hf-Cu polyphenol nanoassembly; Figure 2 It is proved that Hf and Cu bimetallic elements co-exist in the self-assembled HC nanoparticles.
[0068] TEM image of HLC disassembly in a simulated tumor microenvironment provided in Example 2 of the present invention ( Figure 3 ): (a) and (b) are TEM images of Hf-Cu polyphenol and L-Arg nanoassembly HLC after being treated with simulated tumor microenvironment solution (0.1 M H2O2+PBS, pH 5.5) for 4 h and 12 h, respectively; Figure 3 The images showed that the spherical morphology of HLC particles in the simulated tumor microenvironment began to collapse at 4 hours, and after 12 hours, the nanoparticles lost their spherical morphology, expanded and twisted; preliminarily proved that Hf-Cu polyphenol nanoassemblies can respond to disassembly in the acidic tumor microenvironment with high H2O2 expression, thereby being more conducive to deep penetration and retention in the tumor.
[0069] X-ray photoelectron spectroscopy (XPS) diagrams of HB and HLC provided in Examples 1 and 2 of the present invention ( Figure 4 ): (a) is the X-ray photoelectron spectra of Hf-BSA (HB) and HLC; Figures (b)-(f) are the X-ray photoelectron spectra of C, O, Hf, Cu, and N elements in HLC, respectively; Figure 4 The XPS fine structure spectrum shows that the peaks of Hf, O, C, N, and Cu elements are clearly present in the Hf-Cu polyphenol nanoassembly HLC structure. The N peak is mainly derived from the N element in L-Arg. The Hf peak is stronger than the Cu peak, which proves that the content of Hf element is higher than that of Cu element.
[0070] The cloning effect diagram of 4T1 breast tumor cells of HLC provided in Example 2 of the present invention (a) and the statistical data of the survival rate of 4T1 breast tumor cells in different treatment groups (b) are shown in FIG. Figure 5; The 4T1 breast tumor cell cloning effect diagram (a) of HLC provided in Example 2 of the present invention, 1000 4T1 breast tumor cells / well were inoculated in a 6-well plate, and different groups were treated according to the corresponding requirements. The selected experimental conditions are: the X-ray irradiation dose is 4Gy; the concentration of the material is 50μg / ml. By counting the number of clones formed, the cloning rate of the cells can be calculated. Compared with Control+X-ray, HB+X-ray, HC+X-ray and the control group (Control group, HB group, HLC group), the cell survival rate of the HLC+X-ray group is lower, indicating that the HLC+X-ray group has better killing ability for tumor cells; (b) The statistical data of the survival rate of 4T1 breast tumor cells in different treatment groups also prove that the HLC+X-ray group has a stronger killing ability for tumor cells than other groups, and the cell survival rate of the HLC+X-ray group is less than 22%.
[0071] The dose-dependent effect diagram of X-ray radiotherapy sensitization provided in Example 2 of the present invention ( Figure 6 ): (a) Colony formation of 4T1 breast tumor cells treated with Hf-Cu polyphenol nanoassemblies HLC at different X-ray irradiation doses; (b) Survival rate of 4T1 mouse breast cancer cells treated with HLC at different X-ray irradiation doses, HLC concentration: 50μg / mL; Figure 6 It can be seen that with the increase of radiation dose, the killing of tumor cells by Hf-Cu polyphenol nanoassembly HLC is significantly enhanced. Cloning experiments show that the HLC+X-ray group can effectively reduce the radiation dose, and its sensitization ratio (SER10) is 1.29. The dose-dependent toxic effect diagram of HB and HLC on tumor cells provided in Examples 1 and 2 of the present invention ( Figure 7 ); (a) is the cell survival rate of 4T1 mouse breast tumor cells after incubation with different concentrations of HB and HLC for 24 hours. After incubation for 24 hours, the cell survival rate can still reach more than 98% when the concentration of HB is in the range of 50μg / mL. However, when the concentration is in the range of 100-200μg / mL, HLC shows a certain killing effect on 4T1 tumor cells, which may be that copper death has a certain tumor killing effect. In the HB group, there is no tumor cell killing effect when only Hf is present at a concentration of 200μg / mL, which further illustrates that the presence of Cu in the Hf-Cu bimetallic system is also very important, and the synergy of the two metal elements Hf-Cu has potential anti-tumor effects.
[0072] HB@BSA@ provided in Examples 1 and 3 of the present invention 99m Tc(a) and HLC@BSA@ 99mIn vivo SPECT / CT imaging and distribution maps of Tc (c) and (d) ( Figure 8 ). It is used to demonstrate the deep penetration and retention effect of HLC disassembly in tumor microenvironment response, passive targeting effect, and its distribution and metabolic pathway: (a) HB@BSA@ 99m SPECT / CT images of Tc 1h, 3h, and 6h after intravenous (iv) and intratumoral (it) injection. 99 The labeling rate of Tc-labeled HB is 90.99%); (b) HLC@BSA@ 99m SPECT / CT images 1h, 3h, and 6h after Tc intravenous and intratumoral injection ( 99 The labeling rate of Tc-labeled HLC was 88.23%); the results showed that after intratumoral administration, HLC@BSA@ 99m The intratumoral penetration and retention of Tc are higher than those of HB@BSA@ 99m Tc, HB@BSA@ 99m Tc partially leaked out of the tumor at 6 h and entered the liver and spleen metabolic pathway, but HLC@BSA@ 99m No obvious imaging signals were found in the liver and spleen of the Tc group. (cd) Gamma counter quantification of HB@BSA@ of different sizes and compositions 6 hours after administration by two different administration routes (including intravenous iv and intratumoral it). 99m Tc and HLC@BSA@ 99m The distribution of Tc in the main organs and tumors of living mice. After intravenous administration, HLC@BSA@ 99m Tc disassembles in the tumor microenvironment, and the passive targeting (EPR effect) and intratumoral permeability of the 1h group are obvious. As the time is extended to 6h, there is still obvious retention in the tumor site, which is significantly better than HB@BSA@ 99m The intratumoral permeability of Tc. After 6 hours of intratumoral administration, HB@BSA@ 99m Tc and HLC@BSA@ 99m The Tc group had a retention and penetration enhancement effect in the tumor, and HLC@BSA@ 99m The intratumoral retention intensity of Tc group was higher than that of HB@BSA@ 99m Tc group. In general, the quantitative results of gamma counting were consistent with those of SPECT / CT imaging.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a bimetallic nanoassembly, characterized in that: include: A) mixing a phenolic polymer with a surfactant solution; B) mixing the solution obtained in step A) with a hafnium chloride solution; C) mixing the solution obtained in step B), a cross-linking agent and a copper sulfate solution; D) adjusting the pH of the solution obtained in step C) to 7-9, centrifuging and precipitating to obtain Hf-Cu polyphenol nanoassemblies.
2. The method for preparing a bimetallic nanoassembly according to claim 1, characterized in that: Step B) further comprises mixing the solution obtained in step A) with an aqueous solution of hafnium chloride and then adding L-arginine solution.
3. The method for preparing a bimetallic nanoassembly according to claim 2, characterized in that: In step D), the solution obtained in step C) is adjusted to a pH of 7 to 9, preferably 8, with a NaOH solution or an ammonia solution.
4. The method for preparing a bimetallic nanoassembly according to claim 3, characterized in that: Step D) further comprises mixing the Hf-Cu polyphenol nanoassembly with deionized water, adding a BSA solution, centrifuging and washing to obtain BSA-modified HfCu-polyphenol nanoparticles.
5. The method for preparing a bimetallic nanoassembly according to any one of claims 1 to 4, characterized in that: Step D) further comprises subjecting the BSA-modified HfCu-polyphenol nanoparticles to radionuclide 99 Tc labeling; Preferably, the radionuclide labeling comprises: preparing the BSA-modified HfCu-polyphenol nanoparticles into HLC@BSA solution using acetic acid-sodium acetate buffer, adding stannous chloride solution and sodium pertechnetate solution, ultrasonically dispersing and centrifuging to obtain a radionuclide-labeled bimetallic Hf-Cu nano self-assembly.
6. The method for preparing a bimetallic nanoassembly according to any one of claims 1 to 5, characterized in that: The phenolic polymer includes tannic acid; and / or the cross-linking agent is a formaldehyde solution.
7. The method for preparing a bimetallic nanoassembly according to any one of claims 1 to 6, characterized in that: In the hafnium chloride aqueous solution and the copper sulfate solution, the molar ratio of hafnium chloride to copper sulfate is (0.00005-0.0001):(0.00002-0.00004), preferably 0.0001:0.00002.
8. A bimetallic nanoassembly, characterized in that: The bimetallic nanoassembly is Hf-Cu-polyphenol nanoparticles; preferably BSA modified with nuclides 99 Tc-labeled bimetallic Hf-Cu-polyphenol self-assembled particles; Preferably, the molar ratio of Hf to Cu is 2.6:1; And / or, the particle size of the bimetallic nanoassembly is 95-150 nm.
9. Use of the bimetallic nanoassembly obtained by the method for preparing the bimetallic nanoassembly according to any one of claims 1 to 7 or the bimetallic nanoassembly according to claim 8 in preparing tumor therapeutic agents, antibacterial agents or environmental management agents.
10. A tumor treatment device, characterized in that: The invention comprises an X-ray laser and a bimetallic nanoassembly prepared by the method for preparing a bimetallic nanoassembly according to any one of claims 1 to 7 or the bimetallic nanoassembly according to claim 8.
Citation Information
Patent Citations
Template-free hollow tannic acid-iron nano coordination sphere as well as preparation method and application thereof
CN113995837A
Single micelle metal-polyphenol nano material as well as preparation and application thereof
CN116725966A